Influence of electron-electron interactions on supercurrent in SNS structures - Engström, K.; Kinaret, J.; Shekhter, R.I.; Puska, M.; Saarikoski, H. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2003)
We consider a superconductor-normal quantum dot-superconductor structure in which the number of electrons in the dot can be controlled by a gate voltage. We study the effect of electron-electron interactions on the supercurrent between the two superconductors. Using both an analytic model and numerical density functional calculations, we find that Coulomb interactions may serve to make the system quantum mechanically more "rigid", i.e., increasing its sensitivity to phase gradients, hence enhancing the supercurrent through the structure, especially at small phase differences. Accordingly, we find that in this structure the supercurrent can be controlled by the gate voltage.